POLITICS IN THE WORKS OF THE YOUNG MIGUEL REALE, THE THEORIST OF BRAZILIAN INTEGRALISM - Cabral, Gustavo César Machado (2014)
This paper will discuss a relevant topic to Legal History – especially, to the History of Political Ideas. Integralism, a political movement emerged in the 1930s, was the Brazilian representation of the tendency to create a third way, located between liberalism and communism. Its main theorist was Miguel Reale, whose works are best known in the field of Philosophy of Law, and whose political works written in this period have not yet received the same attention. The intention of this article is precisely to discuss the ideas of the young Miguel Reale. Initially, it was included biographical information about the author, and then it was tried to sketch a general profile of Integralism, considering its troubled context. In a third moment, it was focused on a direct analysis of Reale’s works from this period, being selected, from his writings, some points considered most relevant, which are linked to political and economic issues, to the proposed model of State and to the relations between Integralism and Fascism.